(3GdWH Gdcdjs - (3YjSi Hf jMji GdeSjMj GdLQLGfj, CHh Sgd , J (B401 (3g` s ((3eMeO Hf GdMSf Hf Ydj Hf CHj GdaJM GdfbGT s)
(3ChdgG (B:s
(3GdHGH GdSGHY hGdKdGKhf ai GdaUO GdHGH GdChd ai GdMGLI Edi GdWH haGFOJg hJMOjOg hCbSGeg s
(3BNQgG (B:s
(3OhGA jLaa GdHOf hjgRdg jLeY hjYLf hjLaa hjTQH efg cd CSHhY eQI eQGQoG cKjQI s
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B110 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B35s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B150 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1576s
Keywords: (3GdWHs